Pattern, Perception, and Performance: Tripartite Phrases in Academic Paper Titles - Lutz Bornmann; Klaus Wohlrabe (CESifo GmbH, 2025)
This study examines how tripartite phrases in academic paper titles affect citation counts. Tripartite phrases consist of three interconnected elements separated by commas and conjunctions such as pattern, perception, and performance. Analyzing comprehensive datasets from economics (235,330 articles) and medicine and life sciences (93,713 articles), we found that papers with titles including tripartite phrases receive significantly more citations. Papers with tripartite phrases receive on average 3.5 additional citations in economics and 32 additional citations in medicine and life sciences compared to those without, controlling for paper characteristics, journal characteristics, and publication timing. For medical and life sciences papers, this effect persists when controlling for expert-assessed paper quality. The relative share of tripartite titles among the titles of all papers was stable over time at approximately 9% in economics and 4% in medicine and life sciences, suggesting an established stylistic convention.
Keywords: A10; 330; tripartite phrases; academic writing; bibliometrics; citation analysis; paper titles